Technolekt policyjny jako przykład języka specjalistycznego (Conversatoria Linguistica, 2018)
This article attempts to characterize the LSP of the Police as a basic communication tool. The theoretical part starts with defining LSP as a representation of specialist knowledge and a conventionalized semiotic system based on a natural language which serves as an indicator of the level of civilization development and an instrument of professional work and training. Next, the main features of Police LSP are specified as: hermeticism, professionality, maximum expressivity, monosemy, application of artificial semiotic systems and text compression techniques, morphological simplification, multidisciplinarity and multidimensionality. The analytical part of this paper focuses on determining characteristic features of various types of Police LSP and source of terms they use.